2000
DOI: 10.1007/s11661-000-0048-8
|View full text |Cite
|
Sign up to set email alerts
|

Substructural changes during hot deformation of an Fe-26Cr ferritic stainless steel

Abstract: Dynamic softening and substructural changes during hot deformation of a ferritic Fe-26Cr stainless steel were studied. The flow stress increased to reach a steady state in all the cases and the steadystate stress decreased with decreasing Z, the Zener-Hollomon parameter. A constant subgrain size was observed to correspond to the steady-state flow and the steady-state subgrain size increased with decreasing Z. Substructure examinations revealed that elongated, pancake-shaped subgrains formed in the early stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Such a mechanism is common in the superplastic deformation of some high SFE metals, such as Al alloys, [16,17] Mg alloys, [18] and ferritic steels. [19][20][21] The significant effects of initial grain size on the post-DRX recrystallization in different materials has also been reported in a number of studies. [14,22] For example, it has been shown that during annealing of a deformed Al alloy, a transition from DDRX to CDRX can occur with a considerable decrease in the initial grain size.…”
Section: A Dehghan-manshadi and Pd Hodgsonmentioning
confidence: 99%
“…Such a mechanism is common in the superplastic deformation of some high SFE metals, such as Al alloys, [16,17] Mg alloys, [18] and ferritic steels. [19][20][21] The significant effects of initial grain size on the post-DRX recrystallization in different materials has also been reported in a number of studies. [14,22] For example, it has been shown that during annealing of a deformed Al alloy, a transition from DDRX to CDRX can occur with a considerable decrease in the initial grain size.…”
Section: A Dehghan-manshadi and Pd Hodgsonmentioning
confidence: 99%
“…A number of efforts have been devoted to understand the hot deformation behavior and study the microstructural evolution in FSSs, such as 409L FSS [9], 430 FSS (0.028% C, 16.355% Cr) [10], high purified 17%Cr FSS (0.006% C, 17.2% Cr) [11], ultra purified 21%Cr FSS (0.003% C, 20.85% Cr) [12], stabilized 21%Cr FSS (0.004% C, 21% Cr) [13], ultra purified 17%Cr FSS (0.005% C, 17.2% Cr) [14], AISI 430 FSS (0.018% C, 16.5% Cr) [15] and Fe-26Cr FSS [16]. In majority of the studies, however, constitutive equations were based on the Arrhenius-type equation and the assumption that the effect of strain on hot deformation behavior is insignificant.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, others have proposed that new grains formed by dynamic recrystallization (DRX) appeared in some deformation conditions. The dynamic softening process was also explained by a combination of extensive dynamic recovery and limited dynamic recrystallization in the FSSs [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally considered that dynamic recovery (DRV) is the sole dynamic restoration process of ferrite phase (bcc) during deformation at elevated temperature. However, since the 1970s, dynamic recrystallization (DRX) of ferrite has been found to occur in highly pure irons, [2,3] interstitial-free (IF) steels, [4,5,6] ferritic stainless steels, [7,8,9] and low-carbon steels, which deformed in the (F ϩ A) twophase range. [10,11,12] Further, in our study of deformationenhanced transformation of austenite to ferrite in a low-carbon steel, [13] it was found that the occurrence of DRX of ferrite led to the further refinement of ferrite grains after the transformation of austenite to ferrite.…”
Section: Introductionmentioning
confidence: 99%
“…The process described previously is a typical continuous DRX (CDRX) process described in a ferritic stainless steel [8] and low-carbon steels deformed in the (F ϩ A) two-phase region, [10,11,12] the characteristic of which is that the stressstrain curve is nearly flat although a slight decrease after the peak stress strain leads to the formation of substructures. With increasing strain, substructures develop continually, leading to the rotation and coalescence of subgrains.…”
mentioning
confidence: 99%